Optimising the `mid-stage' training and testing process after ACL reconstruction - Buckthorpe, M.; Della Villa, F. (Sports Medicine, 2020)
Outcomes following anterior cruciate ligament (ACL) reconstruction need improving, with poor return-to-sport rates and high risk of secondary re-injury. There is a need to improve rehabilitation strategies after ACL reconstruction, if we can support enhanced patient outcomes. This paper discusses how to optimise the mid-stage rehabilitation process after ACL reconstruction. Mid-stage is a difficult and vitally important stage of the functional recovery process and provides the foundation on which to commence late-stage rehabilitation training. Often many aspects of mid-stage rehabilitation (e.g. knee extensors isolated muscle strength) are not actually restored prior to return-to-sport. In addition, if we are to allow time for optimal late-stage rehabilitation and return-to-sport training, we need to optimise the mid-stage rehabilitation approach and complete it in a timely manner. This paper forms a key part of a strategy to optimise the ACL rehabilitation approach and considers factors more specific to mid-stage rehabilitation characterised in 3 areas: (1) muscle strength: muscle and joint specific, in particular at the knee level, with the knee extensors and flexors and distally with the triceps surae and proximally with the lumbo-pelvic-hip complex, as well as closed kinetic chain strength; (2) altered basic motor patterning (movement quality) and (3) fitness re-conditioning. In addition, the paper provides recommendations on how to implement these into practice, discussing training planning and programming and suggests specific screening to monitor work and when the athlete is able to progress to the next stage (e.g. late-stage rehabilitation criteria).